WRESTLING IS THE MOST EFFECTIVE TOOL FOR EDUCATING THE YOUNGER GENERATION TO BE PHYSICALLY HEALTHY AND MENTALLY MATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the idea that wrestling is the most effective means of educating the younger generation to be physically healthy and mentally mature. Through wrestling, one of the most important tasks facing coaches and professionals is to bring up young people in a healthy and harmonious way, to study in detail.